Analysis of Kinetoplast DNA from Mexican Isolates of Leishmania (L.) mexicana - Hernández-Montes, Omar; González Guzmán, Saúl; Martínez Gómez, Federico; Barker, Douglas C.; Monroy-Ostria, Amalia (Interdisciplinary Perspectives on Infectious Diseases, 2012)
This study analyzed DNA minicircles of Mexican isolates of L. (Leishmania) mexicana to look for genetic differences between strains isolated from patients with diffuse cutaneous (DCL) and localized (LCL) leishmaniasis. The kDNA was analyzed using polymerase chain reaction (PCR), restriction fragment polymorphism analysis of the PCR products (PCR-RFLP) and the PCR products were sequenced. In the PCR with primers specific for the subgenus Leishmania, the Mexican isolates gave higher amplification products than the other L. mexicana complex strains and with specific primers for the L. mexicana complex they were poorly amplified. In the PCR-RFLP analysis with the Eco RV, Hae III, and Mbo I endonucleases, the Mexican isolates displayed similar restriction patterns, but different from the patterns of the other members of the L. mexicana complex. In the phylogenetic tree constructed, the kDNA sequences of the Mexican clones formed two groups including sequences of LCD or LCL clones, apart from the other L. mexicana complex members. These results suggest that the kDNA minicircles of the Mexican isolates are more polymorphic than the kDNA of other members of the L. mexicana complex and have different recognition sites for the restriction enzymes used in this study.